Nitrogen-doped Carbon Dots Derived from Green Algae and Ammonia as Photocatalyst Material - Erna Hastuti; Mutiara; Kurniati; Hikmah (Jurnal Sains Materi Indonesia, 2024)
Carbon dots are a novel carbon-based material with the appealing properties of inexpensive nanomaterials, low toxicity, environmental tolerance, abundance, photostability, and simplicity of synthesis. Carbon dots (CDs) have effectively distinguished themselves from other materials due to their superior properties, such as ultra-small size, good photostability, excellent biocompatibility, and tunable fluorescence properties. This study synthesized carbon dots from green algae using a hydrothermal method at 180 °C and doped with nitrogen. Green algae contain carbohydrates, proteins, and poly-unsaturated fatty acids, allowing them to produce more carbon and be used as a precursor in synthesizing carbon dots. The FT-IR and UV-Vis spectra reveal the distinct functionalization and energy gap between the surface states of CDs and N-CDs. The carbon nanoparticles were then used as photocatalysts to degrade methyl red. The results indicate that nitrogen doping is superior for reducing methyl red and has tremendous potential for environmental applications.